Determinant Factor of Childhood Basic Immunization Compliance during the COVID-19 Pandemic in Jambi City, Jambi Province, Indonesia - Carolina, Anita Rezeki; Efendi, Defi; Maria Dyah Kurniasari (Universitas STRADA Indonesia, 2021)
Background: The coverage of immunization among children in Jambi City decreased during COVID-19 pandemic.Purpose: This study aims to identify the factors that might be associated with basic vaccination compliance among mothers in Jambi, Indonesia.Methods: This study uses a case control design in 5 Jambi City Regions in March-May 2021. The sample in this study is mothers who have children in age 9-24 months. The sampling that is used in this study is cluster sampling with total sample of 506 mothers. The data analysis used in this study is descriptive statistical analysis of univariate, bivariate using chi square test.Results: The results of data analysis showed that the variables related to compliance were perceptions of receiving immunization, attitudes, knowledge, husband's support with p value < 0.01, and distance traveled with p value < 0.05.Conclusion: Effort to improve compliance in the pediatric immunization Pandemic are needed to strengthen mother’s perception, knowledge, attitudes during COVID-19. Analysis with predictive models is highly recommended to determine the odd-ratios and adjusted odd-ratios between factors related to the complying for basic vaccination.